442 Cage Type in Short Segment Transforaminal Lumbar Interbody Fusions is Associated With Alterations in Foraminal Height, but Not Clinical Outcomes. (1st April 2022) - Gibbs, David C.; Viljoen, Stephanus; Toop, Nathaniel; Maggio, Dominic; Oosten, James; Deistler, Kyle; Gilkey, Ty; Farhadi, Francis; Grossbach, Andrew J.
Abstract : INTRODUCTION: Steerable "banana" cages have been shown to increase index level segmental lordosis in short-segment transforaminal lumbar interbody fusion (TLIF) procedures. The same is not true for straight "bullet" cages. While this increase in lordosis is generally thought to be advantageous, a theoretical complication is decreased foraminal height leading to worsened clinical outcomes. METHODS: We retrospectively reviewed one- and two- level TLIFs at a single tertiary care center between 2012 and 2020 with minimum one-year follow-up. Patient report outcome measures (PROMs), revision rates, and radiographic measurements were compared between two cohorts based on cage morphology. RESULTS: 48 patients with 56 straight and 93 patients with 129 steerable cages were identified. Steerable cages were associated with an increase in index level segmental lordosis (7.7 vs 11.8°, p < 0.001) and a decrease in foraminal height (20.3 vs 18.4 mm, p < 0.001). Straight cages were associated with a decrease in index level lordosis (8.2 vs 6.3, p = 0.004) and no significant change in foraminal height (19.5 vs 20.2 mm, p = 0.08). Despite these differences, both cohorts reported improved NRS leg, NRS back, RAND SF-36 pain, RAND SF-36 physical functioning, and ODI scores at last follow-up (p = 0.005). One-year revision rates were similar (straight - 4.2%, steerable - 2.2%, p = 0.88) between cohorts. CONCLUSION: Steerable cages are associated with increased index level segmental lordosis and decreased foraminal height after TLIF. Straight cages are associated with decreased segmental lordosis, but do not correlate with a significant change in foraminal height. Both cage types are associated with significantly improved clinical outcomes.